Complete Blood Count-Derived Inflammation Indices and Retinal Vein Occlusion: A Case-Control Study - Kazantzis,D.; Machairoudia,G.; Kroupis, C.; Theodossiadis, G; Theodossiadis, P; Chatziralli, I (Ophthalmol.Ther., 2022)
INTRODUCTION: This study evaluated complete blood count-derived inflammation indices in patients with retinal vein occlusion (RVO). METHODS: Participants in this case-control study were 54 patients with RVO and 54 age- and sex-matched control subjects. All participants underwent a thorough ophthalmic examination, as well as blood sample testing for complete blood count. Comparison of all parameters derived from complete blood count as well as calculation of specific indices was performed between patients with RVO and controls. RESULTS: Patients with RVO presented significantly higher white blood cell count (p = 0.033), neutrophil count (p = 0.003), neutrophil-to-lymphocyte ratio (NLR, p = 0.002), red cell distribution width (RDW, p = 0.009), mean platelet volume (MPV, p = 0.023), and systemic immune-inflammatory index (SII, p = 0.007) compared to controls. Receiver operator characteristic curve (ROC) analysis showed that NLR was superior to other inflammatory indices, having the greatest area under the curve. The optimal cutoff value for NLR to predict RVO was 2.29 with 46.2% sensitivity and 77.8% specificity. CONCLUSION: Patients with RVO presented increased NLR, RDW, MPV, and SII, providing evidence that inflammation plays an important role in the pathogenesis of RVO. Complete blood cell count-derived indices can be easily calculated and may serve as an easy, simple, and cost-effective tool to evaluate the degree of systemic inflammation in patients with RVO, so as to potentially guide treatment
Keywords: Blood; Retinal Vein Occlusion